(untitled) (Agricultural Engineering, 2024)
The changing climate, causing more frequent abiotic stresses, has generated interest in products that can mitigate the negative impacts of these changes. One such group of preparations includes plant extracts with biostimulant potential, produced using various methods and techniques, including cold plasma and low-pressure microwave discharge. However, there is limited research on how production methods and techniques affect the physical properties of biostimulants, such as density, viscosity, and surface tension. This study aimed to evaluate the impact of the manufacturing process on these properties. The biostimulant was produced via hot water extraction using either cold plasma or low-pressure microwave discharge. Results showed that neither method reduced the surface tension of the biostimulants, but they significantly influenced the viscosity and density. Given these changes in physical properties, further research on droplet spectrum and plant coverage during application is necessary to determine the optimal technical parameters for effective spraying.